2018
DOI: 10.1002/ajcp.12223
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Neighborhood “Come through the Door?” Concentrated Disadvantage, Residential Instability, and the Home Environment for Preschoolers

Abstract: Living in a disadvantaged neighborhood is associated with heightened risk for poor school readiness and health outcomes in early childhood, and the home environment is thought to be a primary mechanism by which neighborhood context impacts preschoolers. This study examined the effects of neighborhood concentrated disadvantage and neighborhood residential instability on the home physical environment and home learning environment for preschoolers in economically disadvantaged families (N = 187). Using structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…Case studies cited above from around the world unite "poverty" with disadvantaged neighborhood. A study conducted by May et al (2018) found that "living in a disadvantaged neighborhood is associated with heightened risk for poor school readiness and health outcomes in early childhood, and the home environment is thought to be a primary mechanism by which neighborhood context impacts preschoolers. "…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies cited above from around the world unite "poverty" with disadvantaged neighborhood. A study conducted by May et al (2018) found that "living in a disadvantaged neighborhood is associated with heightened risk for poor school readiness and health outcomes in early childhood, and the home environment is thought to be a primary mechanism by which neighborhood context impacts preschoolers. "…”
Section: Resultsmentioning
confidence: 99%
“…There are historical, political, social, and economic reasons, which resulted in the formation of disadvantaged neighborhood. Poverty is a common factor which is associated with both formation and consequences of creation of a disadvantaged neighborhood (Brooks-Gunn et al 1997;Jonathan 1991;May et al 2018).…”
Section: Definitionmentioning
confidence: 99%
“…They do, however, complement existing research on the importance of the social environment for cognition in development and on the efficacy of interventions focused on social environments. For example, parents' and children's social embeddedness within their community appears to protect against adverse effects of neighborhood disadvantage (May, Azar, & Matthews, 2018;Witherspoon & Ennet, 2011). Furthermore, social environmental factors like cultural familism and social embeddedness buffer stress-related effects in youth across racial and ethnic identities (Corona et al, 2017) and improve prosocial behaviors and academic achievement (Smith et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a lower-income family may reside in a neighborhood comprised of families with various incomes, or they may reside in a neighborhood of concentrated disadvantage. While the social comparison factors (Festinger, 1954) that may accompany living in a mixed-income neighborhood should not be overlooked, growing up in an area of concentrated disadvantage exerts a direct and tangible effect on children's socioemotional development, above and beyond the effects of familial socioeconomic status (Carpiano et al, 2009;May et al, 2018). However, concentrated disadvantage may also exert an indirect effect on the benefits of an arts education program through its effects on child-level factors, by, for example, limiting a child's access to arts education and thereby restricting their prior experience in the arts.…”
Section: The Ecological or Environmental Contextmentioning
confidence: 99%